Effect of tadalafil on penile nitric oxide synthase and corporal smooth muscle in rats under dutasteride treatment - KABASAKAL, LEVENT (TAYLOR & FRANCIS LTD, 2020)
Aim: To investigate the effect of tadalafil in rats administered with daily dutasteride. Methods: Twenty-four Sprague-Dawley male rats were allocated to three groups as control (group C), dutasteride (group D) and dutasteride plus tadalafil (group D + T). After a month of treatment, serum samples were obtained from rats to measure dihydrotestosterone and total testosterone. Nitric oxide (NO) synthase (NOS) immunoreactivity and levels of NOS enzyme isoforms, NO and cyclic guanosine monophosphate (cGMP) were evaluated in the harvested penile tissues. Also, corporal smooth muscle and collagen were examined. Results: Staining intensities of neuronal NOS and endothelial NOS were significantly lower in group D (p < .05). They were similar between group C and group D + T. Immunoreactivity of inducible NOS was observed higher in group D than group C (p = .01) whereas group D + T had the highest iNOS (p<.001). ELISA revealed similar outcomes in terms of NOS enzyme isoform levels. The mean of smooth muscle to collagen ratio was the lowest in group D (p < .001) and it was similar among group C and group D + T (p = .072). Group D had the lowest cGMP and NO levels (p < .05) and they did not differ between group C and group D + T (p>.05). Group D and group D + T had significantly decreased dihydrotestosterone and increased testosterone, compared to group C (p < .001). They were similar between group D and group D + T. Conclusion: Daily treatment with tadalafil improves dutasteride-induced changes in rat penis.
Keywords: Dutasteride; erectile dysfunction; tadalafil; nitric oxide synthase; rat; BENIGN PROSTATIC HYPERPLASIA; URINARY-TRACT SYMPTOMS; 5-ALPHA-REDUCTASE INHIBITOR DUTASTERIDE; ERECTILE FUNCTION; ENLARGEMENT SECONDARY; SEXUAL FUNCTION; DUAL INHIBITOR; EFFICACY; MEN; SAFETY